2022
DOI: 10.1093/jac/dkac311
|View full text |Cite
|
Sign up to set email alerts
|

Strain-to-strain variability among Staphylococcus aureus causing prosthetic joint infection drives heterogeneity in response to levofloxacin and rifampicin

Abstract: Introduction Levofloxacin and rifampicin are the preferred treatment for prosthetic joint infection (PJI) caused by Staphylococcus aureus, especially when managed with implant retention (DAIR). However, a significant variability of success has been reported, which could be related to intrinsic characteristics of the microorganism. Our aim was to evaluate the variability in the anti-biofilm response to levofloxacin and rifampicin in a clinical collection of S. aureus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In addition, it has been suggested that the type of strain, the origin and the environmental conditions may impact the level of biofilm production by L. monocytogenes independently of the planktonic growth rate [ 80 ]. On the other hand, the genotypic and phenotypic characteristics of S. aureus strains may be responsible for the variability in biofilm formation [ 81 ]. Furthermore, a wide range of virulence pathways related to infectivity, toxin generation and antimicrobial resistance are associated with the strain variation of the bacteria [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that the type of strain, the origin and the environmental conditions may impact the level of biofilm production by L. monocytogenes independently of the planktonic growth rate [ 80 ]. On the other hand, the genotypic and phenotypic characteristics of S. aureus strains may be responsible for the variability in biofilm formation [ 81 ]. Furthermore, a wide range of virulence pathways related to infectivity, toxin generation and antimicrobial resistance are associated with the strain variation of the bacteria [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature support for this is minimal. While levofloxacin and rifampin are commonly combined for orthopedic infections, such as prosthetic joint infections (PJI), no studies compare their efficacy against planktonic bacteria vs. biofilms (Meléndez-Carmona et al, 2022 ). Nevertheless, a review of other studies indicates that biofilms are still typically more tolerant to combination antibiotic treatments than planktonic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when combined with another antibiotic effective against biofilms, such as levofloxacin, significant antimicrobial efficacy is probable. Additionally, Meléndez-Carmona et al ( 2022 ) performed biofilm studies specifically on a levofloxacin + rifampin combination. They demonstrated that the combination had high efficacy with CDC reactor-grown biofilms (48 h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More insight is needed regarding patients who do not seem to benefit of rifampicin combination therapy. Apart from the question which Gram positive microorganisms should be treated with rifampicin combination therapy, factors like differences in strain variability [53], joint differences [22], and achieving adequate serum levels should be taken into account. In addition, the duration of infection should be considered when evaluating the efficacy of rifampin.…”
Section: Expert Opinionmentioning
confidence: 99%